PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN NASABAH TABUNGAN BATARA PADA PT.BANK TABUNGAN NEGARA (PERSERO) KANTOR CABANG JAMBI - M. Arjun (Fakultas Hukum dan Ekonomi Bisnis, 2024)
This study aims to analyze the quality of service provided to Batara Savings customers at PT. Bank Tabungan Negara (Persero) Jambi Branch, customers’ decisions to save, and the influence of service quality on these decisions. The study uses a survey method, which is an investigation aimed at obtaining facts and factual information related to social, economic, or political institutions (Mohamad, 2003: 56).The survey approach is explanatory, where the collected data is analyzed to explain causal relationships or correlations between variables and test hypotheses. Data analysis was conducted using simple regression with hypothesis testing through the t-test statistical method.The results show that service quality significantly influences customers’ decisions. This is indicated by the value of t-calculated > t-table and a significance level (p-value) < 0.05. A correlation value of 0.991 indicates a very strong relationship between service quality and customers’ decisions. Therefore, service quality is proven to be a crucial factor in influencing customers’ decisions to save at PT. Bank Tabungan Negara (Persero) Jambi Branch.